Determination of Analgesics (Dipyrone and Acetaminophen) in Pharmaceutical Preparations by Cyclic Voltammetry at a Copper(II) Hexacyanoferrate(III) Modified Carbon Paste Electrode - Teixeira, Marcos F. S. [UNESP]; Marcolino-Junior, Luiz H.; Fatibello-Filho, Orlando; Moraes, Fernando C.; Nunes, Ronaldo S. (Bentham Science Publ Ltd, 2009)
Copper(II) hexacyanoferrate(III) (CuHCF) modified carbon paste electrode was used for the electroanalytical determination of dipyrone and acetaminophen in pharmaceutical preparations by cyclic voltammetry. Several parameters were investigated for the optimization of the sensor such as composition of the electrode, electrolytic solution, effect of pH, scan rate of potential and interference. The best conditions were found for an electrode composition in mass of 20% CuHCF, 55% graphite and 25% mineral oil in acetate buffer containing 0.05 mol L(-1) of NaCl. The analytical curve was linear in the dipyrone and acetaminophen concentration ranged from 1.25 x 10(-5) mol L(-1) to 1.23 x 10(-3) and 2.84 x 10(-4) to 2.59 x 10(-3) mol L(-1) respectively, being successfully applied to the determination of dipyrone and acetaminophen in pharmaceutical preparations. The CuHCF modified carbon paste electrode presented comparable results to those obtained using iodimetry and ultraviolet spectrophotometry methods, respectively.
Keywords: Modified carbon paste electrode; Copper(II) hexacyanoferrate(III); Voltammetric determination; Analgesics; Pharmaceutical preparations